Curcumin inhibits the proteolytic process of SREBP‐2 by first inhibiting the expression of S1P rather than directly inhibiting SREBP‐2 expression. Issue 1 (8th November 2020) - Li, Yongnan; Wu, Shuodong
Abstract: Many studies have demonstrated that curcumin can downregulate mRNA levels of sterol regulatory element‐binding proteins (SREBP‐2); however, our study did not find similar results. This study was designed to demonstrate that curcumin inhibits the proteolytic process of SREBP‐2 by first inhibiting the expression of membrane‐bound transcription factor site‐1 protease (S1P) rather than directly inhibiting SREBP‐2 expression. After curcumin treatment, Caco‐2 cells were collected to observe the dose‐ and time‐dependent dynamics of precursor and mature SREBP‐2, transcription factor‐specific protein 1 (SP‐1), and SREBP cleavage‐activating protein (SCAP). After curcumin treatment, SREBP‐2 distribution was detected in the cells and S1P protein expression was examined. Curcumin could downregulate mRNA levels of SREBP2, SP‐1 and SCAP, but it did not simultaneously downregulate the expression of precursor SREBP‐2 (pSREBP‐2) and SCAP. Curcumin can inhibit the proteolytic process of SREBP‐2, reduce the production of mature SREBP‐2 (mSREBP‐2), and change the cellular distribution of SREBP‐2. The inhibitory effect of curcumin on SP‐1 protein expression is short‐acting. Curcumin could downregulate the mRNA and protein expression of S1P, but has no obvious inhibitory effect on the mRNA and protein expression of S2P (site‐2 protease). Curcumin can inhibit the SREBP‐2 proteolytic process to reduce mSREBP‐2 which functions as a transcription factor, affecting the regulation of cholesterol metabolism‐related genes. Curcumin does not directly inhibit the expression of mSREBP‐2 protein, and it has no such inhibitory effect for at least a short period of time, although curcumin does reduce the amount of mSREBP‐2 protein. S1P is a key protease in the hydrolysis of pSREBP‐2 into mSREBP‐2. Therefore, curcumin may decrease the amount of mSREBP‐2 by directly inhibiting the expression of S1P mRNA and protein. Abstract : This study found for the first time that although curcumin could indeed downregulate the expression of SREBP‐2 mRNA, it did not down‐regulate the expression of SREBP‐2 protein. This discovery is different from all previous studies on the relationship between curcumin and SREBP‐2, which is a new discovery. In addition, this study also found that curcumin inhibited the process of SREBP‐2 proteolysis, possibly by inhibiting the expression of S1P, which is also a new discovery and has not been reported.